Enhancing Mentors’ Effectiveness: The promise of the Adaptive Mentorship© model - Ralph, Edwin; Walker, Keith (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
The Adaptive Mentorship (AM) model is described and implications are raised for its wider implementation. The researchers derived the AM model from earlier contingency leadership approaches; and during the last two decades, they have further refined AM through application and research. They suggest the benefits and transferability of AM to any field to assist protégés in developing professional proficiency in their respective contexts.